The Role of Multicultural Education and Social Media in the Affirmation of Democratic Society - Demush Bajrami; Arafat Shabani (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
in the overall educational process. In this process, classrooms and schools become models of democracy and equality among people in society. This study contributes to the knowledge on the moderating role of social media usage in the relationship between multicultural experiences and creativity based on experiential learning theory. The study presents the relationship among multicultural experiences, cultural intelligence, and creativity. Moreover, by investigating the moderating roles of informational and socializing social media usage, the authors presented that an IT contingent view of multicultural experiences is helpful in understanding the relationship between multicultural experiences and cultural intelligence. The abilities for efficient functioning of different cultural elements are issues that need to be addressed properly. In order for the students to function efficiently and as a whole in a democratic society, they have to learn about differences and injustices which occur at certain times and under given circumstances. Otherwise, our society will not be able to overcome these differences and injustices.
Keywords: I23; 330; multicultural education; social media; learning with community and teaching in community